Impoliteness and Power in U.S. Political Campaign Debates: The Case of Donald Trump - Ahmad Wijanarko; Thomas Joko Priyo Sembodo (Universitas Gadjah Mada, 2018)
This research examines impoliteness strategies in the context of political campaign debates by the presidential candidates, particularly by Donald Trump against other candidates. The data used in this research, taken from the last three National Republican debates, were Donald Trump’s utterances in which he employed impoliteness strategies. The data were analyzed using Garcia-Pastor’s (2008) impoliteness strategies. The results show that Donald Trump employed the negative-face oriented strategies much more frequently (66.15%) than the positive-face oriented strategies (33.85%). The negative-face oriented strategy ‘state the communicative act(s) as common or shared knowledge’ was the most frequently used (30.38%). These results suggest that for the purposes of asserting power in the debates, Donald Trump tends to use negative-faced oriented impoliteness strategies in his political debates.